2009
DOI: 10.1074/jbc.m109.038513
|View full text |Cite
|
Sign up to set email alerts
|

Cyanochromes Are Blue/Green Light Photoreversible Photoreceptors Defined by a Stable Double Cysteine Linkage to a Phycoviolobilin-type Chromophore

Abstract: Phytochromes are a collection of bilin-containing photoreceptors that regulate a diverse array of processes in microorganisms and plants through photoconversion between two stable states, a red light-absorbing Pr form, and a far red light-absorbing Pfr form. Recently, a novel set of phytochrome-like chromoproteins was discovered in cyanobacteria, designated here as cyanochromes, that instead photoconvert between stable blue and green light-absorbing forms Pb and Pg, respectively. Here, we show that the distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
147
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(161 citation statements)
references
References 61 publications
(146 reference statements)
12
147
2
Order By: Relevance
“…2A). Irradiation of Pg with green light restored the Puv spectrum with a broad absorption maximum at 382 nm, results similar to those previously reported for recombinant UirS/Slr1212-GAF (18). Absorption and difference spectra of UirS-GAF expressed in Synechocystis cells were nearly identical to those of the E. coli-expressed version (Fig.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…2A). Irradiation of Pg with green light restored the Puv spectrum with a broad absorption maximum at 382 nm, results similar to those previously reported for recombinant UirS/Slr1212-GAF (18). Absorption and difference spectra of UirS-GAF expressed in Synechocystis cells were nearly identical to those of the E. coli-expressed version (Fig.…”
Section: Resultssupporting
confidence: 88%
“…UirS belongs to a CBCR subfamily with two conserved Cys residues within its phycocyanobilin (PCB)-binding GAF domain (14), with other notable examples being Synechocystis SyPixJ/TaxD1/Sll0041 (5,15) and TePixJ/Tll0569 and Tlr0924 from Thermosynechococcus elongatus (14,16,17). Previous studies have shown that the region containing TM helices is responsible for ethylene binding in UirS (12), whereas its GAF domain can bind to the linear tetrapyrrole PCB to yield a violet/green light-switchable CBCR (18).…”
mentioning
confidence: 99%
“…This energy transfer requires the two chromophores in close proximity and indicates that the holo-GAFs aggregate in solution. 14 In agreement, the solutions contain exclusively dimers as determined by gel filtration (Fig. S7 †).…”
Section: Autocatalytic Chromophorylation Of Gafs With Pebsupporting
confidence: 70%
“…6 Some CBCRs contain doubly linked PCB or phycoviolobilin (PVB) chromophores. 3,4,[12][13][14][15] Such GAF domains of Nostoc punctiforme ATCC 29133 and one of Cph2 of Synechocystis sp. PCC 6803 have been tested for PEB chromophorylation.…”
Section: Introductionmentioning
confidence: 99%
“…sanger.ac.uk) and were used for phylogenetic analysis. ATG1 and ATG13 protein sequences were aligned by ClustalX (Chenna et al, 2003) under the default settings and compared by MrBayes version 3.1.2 (Ronquist and Huelsenbeck, 2003) using the proportion of invariable sites g rate model and the mixed amino acid model as described (Ulijasz et al, 2009). The program was run for 1,000,000 generations, and the first 25% (337,500 generations) was discarded as "burn in" after checking that the log likelihood values had reached a plateau.…”
Section: Identification and Phylogenetic Analysis Of Atg1 And Atg13 Gmentioning
confidence: 99%